Sentence Forming Errors Based on the Valence of German Verbs in Student Writing in the Aufsatz II Course - Brenda Avinda; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This study aims to describe the form of  sentence errors based on the verb valency in the student's essay in the Aufsatz II course and identify the factors that influence the students to make these kind of mistakes. This research used qualitative descriptive method. The data source of this research were the students of the German Literature Department, Universitas Negeri Malang class of 2017 Offering C. The data used in this research are sentence errors based on the verb valency found on the student’s essays and interview results. The results of this research indicate that: (1) Students made mistakes in writing sentences based on the verb valency, with the form of complements errors, such as of Nominativergänzung, Akkusativergänzung, Dativergänzung, Präpositivergänzung, Situativergänzung, Direktivergänzung, sentence errors with reflexive Verben, errors in adding sentence constituents, verb selection errors, and sentence without verb errors, (2) factors that cause those errors were difficulty in learning the German grammar, difficulty in determining the complements required by the verb, Indonesian interference, and rarely practice writing in German.